74. Adaptive Deep Brain Stimulation (ADBS) tested clinically in a patient with advanced Parkinson Disease. Issue 1 (January 2015) - Arlotti, M.; Rosa, M.; Rossi, L.; Marceglia, S.; Cogiamanian, F.; Ardolino, G.; Carrabba, M.G.; Rampini, P.M.; Priori, A.
<x xml:space="preserve">Abstract</x> Conventional deep brain stimulation DBS (cDBS) could be optimized by adapting the stimulation to the patient's clinical state marked by a control variable (i.e. adaptive DBS). Local field potentials (LFPs) recorded from DBS electrodes correlate with the patient's clinical state and can be a reliable control variable for aDBS. We developed an external portable aDBS device controlled by LFPs and we present its clinical assessment in a freely moving PD patient. The 5th and the 6th day after the DBS electrodes implant in the subthalamic nucleus, the patient, after the standard antiparkinsonian medication, underwent 2 h of cDBS and 2 h of aDBS, respectively. The patient was not aware of the DBS type. The motor state was evaluated by a blinded neurologist through the UPDRS motor scale (part III), and dyskinesia scale (Rush filming protocol). Whereas the UPDRS III score was the same during aDBS and cDBS, the dyskinesias were less severe by 57.59% during aDBS compared to cDBS. The aDBS device controlled better the motor fluctuations than cDBS, reducing dyskinesias. This study represents a proof of aDBS application for PD.